Black Pepper’s Anti-Aging and Chemoprevention Properties: A Review - Endah (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2023)
The possible uses of black pepper, a common spice used for cooking, have been expanded. Despite countless studies on its advantageous biological effects, it would be difficult to determine its effectiveness as an anti-aging and chemo-preventive medication. Piperine, chavicine, caryophyllene, and sabinene are a few examples of black pepper components that exhibit pharmacological characteristics. This article reviews black pepper's main ingredients and discusses how effective it is at preventing aging and cancer. Using Google Scholar, PubMed, and Medline for our electronic research, we screened pertinent papers from scientific journals. To help with the explanation in the narrative, all the data was compiled and summarized into tables and graphs. Overall, the anti-aging properties of black pepper and its constituents are exhibited through several pathways, including senescence prevention, antioxidant protection, control of ROS levels, and the inhibition of aging-related enzymes. Additionally, cell cycle regulation, antiangiogenic and anti-metastatic action, apoptosis induction, and the suppression of carcinogenesis are some of the mechanisms utilized in cancer prevention activities. It has been shown to have synergistic effects on several cancer cells when combined with doxorubicin. According to these studies, black pepper could be considered for development as an anti-aging and chemo-preventive agent.